Correlation between leukocytospermia and oxidative stress in male partners of infertile couples with leukocytospermia - Aggarwal, Richa; Puri, Manju; Dada, Rima; Saurabh, Gyan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The last century has seen rapid advances in the diagnosis and management of male infertility but still the cause eludes us in a majority of cases. The World Health Organization (WHO) has defined leukocytospermia as >1 million WBC/mL of semen. However, the clinical significance of increased leukocyte infiltration in semen, that is, leukocytospermia, is currently a subject of controversy. Evidence from several recent studies indicates that leukocytospermia could significantly contribute to male infertility. Of the many causes of male infertility, oxidative stress has been identified as one factor that affects fertility status and thus, has been extensively studied in recent years. A study was conducted to evaluate the relationship between leukocytospermia and oxidative stress. Methods: 88 men with leukocytospermia were included in the study. Semen parameters, no. of pus cells present and oxidative stress were noted. The correlation between leukocytospermia and ROS level was found using Pearson correlation coefficient. Results: Significant positive correlation (r = 0.882, P <0.001) was observed between leukocytospermia and oxidative stress suggesting leukocytes are the main source of Reactive Oxygen Species (ROS) in semen. Conclusions: Significant positive correlation between oxidative stress and leukocytospermia was found in this study suggesting the need of further robust clinical trials to evaluate the role of antioxidants in improving the fertility outcome in infertile men with pyospermia.